The differences of chemical learning outcomes using students work sheet and question cards with NHT type of cooperative models in salt hydrolysis - Gelis Juliandini; Zainuddin Muchtar (Pascasarjana Universitas Negeri Medan, 2018)
This study aimed to determine the differences in chemistry learning results by Numbered Heads Together (NHT) type of cooperative model. This model used student worksheet media compared to question card media on salt hydrolysis. The results shown that there were differences in the learning outcomes in SMA N 1 Perbaungan 2016/2017. The analysis data shown for the gain value in the first experiment class reached 73.19% and the second experiment class 67.57%. The data processing obtained the average value of pre-test and post-test in the first experiment class (33.78) and (82.42) respectively. In the second experiment class cheieved the average value of pretest (33.48) and posttest (78.48). The difference in increasing learning outcomes achieved 5.62%.Keywords:learning outcomes; learning media; numbered heads together; salt hydrolysis